MIRERC(A) 033/2025: Impact of Digital Connectivity on family well-being in Kibera: A Participatory Approach - Mutwiri, Antony; Dr. Sakshi Ghai (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
This study examines the impact of affordable high-speed internet access on youth and family well-being in Kibera, one of Nairobi’s largest informal settlements. Despite the rapid expansion of digital technologies, much of the research on their effects remains focused on Western contexts, leaving a significant knowledge gap in Africa. This study seeks to address this gap by assessing the influence of broadband connectivity on key well-being indicators, including mental health, family dynamics, education, and employment opportunities. Additionally, it aims to develop a culturally relevant framework for measuring digital well-being in the Global South and provide empirical evidence to inform policies on digital inclusion and socio-economic development.